Synthesis and spectroscopic characterization of cyclobutyl hydantoins - Caturelli Kuran, Juan Alberto (2018)
The hydantoin moiety has proved to be an important pharmacophore that confers a wide range of biological properties to different derivatives. Thus, synthetic methods have been developed to obtain such molecules. Herein, we describe the heterocyclization process to obtain imidazolidine-2,4-diones (hydantoin compounds) from methylcyclobutyl ketones and cyclobutanones derived from (−)-(1S)-α-pinene and (−)-(1S)-verbenone through the Bucherer-Berg reaction. The methylcyclobutyl hydantoins and the spirohydantoin obtained were fully characterized, determining their absolute stereochemistry by nuclear magnetic resonance experiments and theoretical calculations.